2000
DOI: 10.5380/avs.v5i1.3892
|View full text |Cite
|
Sign up to set email alerts
|

HISTOPATOLOGIA COMPARATIVA EM FÍGADOS DE BOVINOS, BUBALINOS E OVINOS INFECTADOS POR Fasciola hepatica

Abstract: Através técnicas de rotina para histopatologia foram examinados fígados de bovinos, bubalinos e ovinos infectados por Fasciola hepatica. As colorações utilizadas foram Hematoxilina- Eosina, Tricrômico de Schorr, Tricrômico de Mallory e Azul de Toluidina. As principais lesões observadas foram cortes de parasitas em ductos biliares, fibrose portal, hiperplasia de ducto biliar, fibrose de parede de ducto biliar e infiltração por linfócitos, plasmócitos, eosinófilos e neutrófilos. Lesões de ductos biliares mais ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 1 publication
0
4
0
4
Order By: Relevance
“…Regarding the eosinophilic infiltration, Bostelmann et al (2000) also found discrete infiltration of eosinophils in bovine livers with Fasciola sp. and related moderate eosinophilic infiltration in theirs samples.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Regarding the eosinophilic infiltration, Bostelmann et al (2000) also found discrete infiltration of eosinophils in bovine livers with Fasciola sp. and related moderate eosinophilic infiltration in theirs samples.…”
Section: Discussionmentioning
confidence: 94%
“…Kishida et al (2013) found papillary and glandular hyperplasia of the biliary epithelium in liver obtained from meat inspection in Japan and found moderate biliary epithelial hyperplasia in 33,33% samples following by 66,66% severe. However, Bostelmann et al (2000) evaluated bovine liver samples condemned of fasciolosis from a slaughterhouse in Parana State, Brazil, and found a moderate hyperplasia of the biliary ducts in all the evaluated samples. in their studies also found a moderate intensity of ductal hyplerplasia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A doença é causada por Fasciola hepatica, parasito de grandes e pequenos ruminantes e várias espécies de animais silvestres e domésticos (SILVA SANTOS; SCAINI; RODRIGUES, 1992;MARQUES;SCROFERNEKER, 2003;ARAÚJO et al, 2007;AMOR et al, 2011). A ação do helminto causa prejuízo econômico à pecuária mundial devido à condenação de fígados dos animais afetados (BOSTELMANN et al, 2000;MWABONIMANA et al, 2009;BALA;GARBA;YAZAH, et al, 2011;BERNARDO et al, 2011;OZUNG;OWAI;ONI, 2011). Paralelamente é registrada queda na produção, atraso no crescimento e mortalidade.…”
Section: Introductionunclassified